O consentimento da ofendida como excludente de ilicitude no caso do crime do artigo 24-A da Lei Maria da Penha: uma análise a partir do contexto legal de proteção da mulher no ordenamento jurídico (Publicatio UEPG: Ciências Sociais Aplicadas, 2022)
In 2018, Law 13.641/2018 came into force, which inserted article 24-A into the Maria da Penha Law, which now defines as a crime the non-compliance with decisions on urgente protective measures provided for in Maria da Penha Law, with punishment for detention between three months and two years. Said law aims to increase the protection of women victims of domestic violence, since it is common for the agressor to fail to comply with the protective measure. Nonetheless, it often happens that the victim herself welcomes the agressor again, allowing the non-compliance with the protective measure, which occurs for a number of reasons. The problem that arises from this dynamic involves, within the theory of crime, the (im)possibility of applying the consent of the offended as a supralegal cause of exclusion od illicitness as opposed to the legal protection objectives of the Maria da Penha Law. In this sense, the presente work aims to analyze the legal nature of the Maria da Penha Law from its historical – legal context, to understand the consente of the offended as a supralegal cause of exclusion of illegality and to analyze the (im)possibility of aplication of such cause in relation to the crime of article 24-A of the Maria da Penha Law. To this end, a bibliographic and jurisprudential review will be use, especially the judgment of the Supreme Federal Court of ADI n. 4424/2012, analyzing the arguments of this decision about the vulnerability of the victim and the effective state protection against the theory of the consente of the offended. Contradicting the arguments it was observed that the application of the legal provision is permeated by contradictions, but should always be observed seeking efective state protection and the best option for women in situations of domestic violence.